2020
DOI: 10.1002/wcc.652
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Annular Mode: Variability, trends, and climate impacts across the Southern Hemisphere

Abstract: The Southern Annular Mode (SAM) is the leading mode of extratropical Southern Hemisphere climate variability, associated with changes in the strength and position of the polar jet around Antarctica. This variability in the polar jet drives large fluctuations in the Southern Hemisphere climate, from the lower stratosphere into the troposphere, and stretching from the midlatitudes across the Southern Ocean to Antarctica. Notably, the SAM index has displayed marked positive trends in the austral summer season (st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
169
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(249 citation statements)
references
References 198 publications
(467 reference statements)
24
169
0
Order By: Relevance
“…Hence, springtime ozone anomalies in Antarctica can be used as a predictor of subsequent summer precipitation for South America and Australia. A similar link between ozone anomalies and precipitation has also been established for Antarctica [ 34 ].…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionssupporting
confidence: 61%
“…Hence, springtime ozone anomalies in Antarctica can be used as a predictor of subsequent summer precipitation for South America and Australia. A similar link between ozone anomalies and precipitation has also been established for Antarctica [ 34 ].…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionssupporting
confidence: 61%
“…The SAM is the primary mode of surface climate variability in the Antarctic and Southern Ocean region (Gong and Wang 1999). It not only responds to stratospheric ozone change but also to the effects of tropospheric global warming (Wang and Cai 2013) and other large-scale climate modes, including the El Niño Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) (Fogt and Marshall 2020). Dennison et al (2015) showed that the persistence and variability of the stratospheric SAM is enhanced by ozone depletion, and this leads to longer lasting coupling between the stratosphere and troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these winds play a major role in driving the ocean circulation, and the uptake of carbon and heat (e.g., Hall & Visbeck, 2002; Sen Gupta & England, 2006; Toggweiler & Russell, 2008). In recent years, much attention has been paid to an intensification and poleward shift of these westerlies over the last four decades (e.g., Swart & Fyfe, 2012; Swart et al, 2015; Thomas et al, 2015; Thompson et al, 2011), the connections with the southern annular mode (e.g., Fogt & Marshall, 2020), and the wider impacts on the atmosphere and oceans (e.g., Le Quere et al, 2007; Roemmich et al, 2007; Waugh et al, 2013). However, this attention has focused primarily on changes in the zonal‐mean winds, and longitudinal variations have been largely overlooked.…”
Section: Introductionmentioning
confidence: 99%